The role of stakeholder banks in the European banking systems - Kalmi, Panu (Palgrave Macmillan, Cham, 2017)
Socially oriented financial institutions have an equally long history than profit-oriented financial institutions in Europe. Stakeholder banks occupy a unique and important position in the European banking sector and they have been credited to stabilize the financial market. Changes in financial markets have also caused significant changes in the operations of stakeholder-oriented institutions, leading to significant convergence of the profit-maximizing sector and the stakeholder banks. At the same time, stakeholder banks have remained true to many of their original characteristics. The tensions between regulatory and competitive pressures on the one hand, and the need for a more diverse financial sector on the other hand will continue to characterize the European banking market for years to come.
Keywords: fi=Taloustiede|en=Economics|